Infant product‐related injuries: comparing specialised injury surveillance and routine emergency department data - Kirsten Vallmuur; Ruth Barker (Elsevier, 2016)
Abstract Objective: To explore the potential for using a basic text search of routine emergency department data to identify product‐related injury in infants and to compare the patterns from routine ED data and specialised injury surveillance data. Methods: Data was sourced from the Emergency Department Information System (EDIS) and the Queensland Injury Surveillance Unit (QISU) for all injured infants between 2009 and 2011. A basic text search was developed to identify the top five infant products in QISU. Sensitivity, specificity, and positive predictive value were calculated and a refined search was used with EDIS. Results were manually reviewed to assess validity. Descriptive analysis was conducted to examine patterns between datasets. Results: The basic text search for all products showed high sensitivity and specificity, and most searches showed high positive predictive value. EDIS patterns were similar to QISU patterns with strikingly similar month‐of‐age injury peaks, admission proportions and types of injuries. Conclusions: This study demonstrated a capacity to identify a sample of valid cases of product‐related injuries for specified products using simple text searching of routine ED data. Implications: As the capacity for large datasets grows and the capability to reliably mine text improves, opportunities for expanded sources of injury surveillance data increase. This will ultimately assist stakeholders such as consumer product safety regulators and child safety advocates to appropriately target prevention initiatives.